Discovery of genes that positively affect biomass and stress associated traits in poplar - Georgieva, Tatyana; Yordanov, Yordan; Yordanova, Elena; Khan, Md Rezaul Islam; Lyu, Kaiwen; Busov, Victor (Frontiers in Plant Science, 2024)
Woody biomass provides an serves as a renewable resource for various industries, including pulp and paper production, construction, biofuels, and electricity generation.alternative feedstock for production of biofuels and gasification for the generation of electricity. However, the molecular mechanisms behind biomass traits are poorly understood, However, despite its economic and ecological importance, the underlying molecular mechanisms of biomass-related traits are poorly understood, which significantly curtails the speed and efficiency of their improvement. We used activation tagging to discover genes that can positively affect tree biomass-associated traits. We generated and screened under greenhouse conditions a population of 2,700 independent activation tagging lines. A total of 761 lines, which had significantly and positively affected at least one biomass-associated trait, were discovered. The tag was positioned in the genome for forty lines which were affected in multiple traits and activation of proximal genes validated for a subset. For two lines we fully recapitulated the phenotype of the original lines through overexpression. Moreover, the overexpression led to more pronounced and additional improvements, not observed in the original lines. Importantly, the overexpression of a Fasciclin-like gene (PtaFLA10) and a Patatin-like gene (PtaPAT) was found to substantially improve biomass, with a 40% increase in dry-stem weight, and enhance drought tolerance, respectively. Additionally, PtaPAT overexpression increased cellulose content, which is crucial for biofuel production. Our work shows that the activation tagging approach applied even on a non-genome saturation scale in a poplar tree can be successfully used for the discovery of genes positively modify biomass productivity. Such dominant forward genetics approaches can aid in biotechnological manipulation of woody biomass traits and help unravel the functions and mechanisms of individual genes, gene families, and regulatory modules.